Transmission Dynamics of Monkeypox Virus With Age-Structured Human Population: A Mathematical Modeling Approach - Walter Okongo; Jeconia Abonyo Okelo; Duncan Kioi Gathungu; Stephen Edward Moore; Stanley Aguegboh Nnaemeka (Journal of Applied Mathematics)
This study presents a deterministic mathematical model of monkeypox disease transmission dynamics with an age-structured human population divided into two subgroups of children (Group 1) and adults (Group 2). Two equilibrium points, monkeypox-free, E0, and a unique monkeypox-endemic equilibrium point, E1, are established. The age-structured monkeypox basic reproduction number, ℝ0, is computed using the next-generation matrix approach and established to be ℝ0=1.2448. The Lyapunov functions are constructed; together with LaSalle’s invariance principle, the monkeypox-free equilibrium point, E0, is established to be globally asymptotically stable whenever ℝ0≤1, as confirmed by the Lyapunov stability method, and the monkeypox-endemic equilibrium point, E1, is globally asymptotically stable whenever ℝ0>1. Sensitivity analysis of the threshold quantity ℝ0 is performed using the Latin hypercube sampling method and Pearson’s partial rank correlation coefficient, and the results showed that the parameters β11,β22,μ,ν1,Λ1,ν2 were the most sensitive to the spread of monkeypox infection in an age-structured population. It is, therefore, suggested that the rate of monkeypox infection can be reduced by ensuring that the rate of interaction between susceptible children and infected children and between susceptible adults and infected adults is minimized. Moreover, the spread of monkeypox infection can be curbed by emphasizing controls such as early diagnosis and treatment and hospitalization of critically ill infectives.